The Impact of Rural Water Supply and Sanitation on Economic Growth in South Asia - Madadeniya, M. G. C. N. (H. : ĐHKT, 2020)
"Clean water and sanitation" is one of the 17 Sustainable Development Goals set by the United Nations, and the achievement of this goal is crucial for rural South Asia which accounts for around one third of the world’s rural population. Clean water and sanitation facilities reinforce economic growth by creating a healthy labour force, increasing environmental sustainability and supporting economic activities in all sectors of an economy. This study aims to analyse the impact of rural people’s access to clean water and sanitation facilities on economic growth in South Asia, as the lack of scientific studies focusing on the particular issue for South Asia is a gap in existing literature. A panel data econometric analysis was conducted including four South Asian countries, for the period 1991-2015. The findings of the panel regression indicated that the rural population’s access to improved water sources and improved sanitation facilities has no significant impact on the region’s economic growth during the period studied. However, Granger causality analysis showed that rural population’s access to improved sanitation facilities Granger causes economic growth. Further, it revealed that rural population’s access to improved water sources as well as capital growth Granger cause rural population’s access to improved sanitation facilities. Given that capital growth had a significant positive impact on economic growth in the regression analysis, more capital investments in the rural water supply and sanitation projects are thus encouraged for the South Asian region to reap growth benefits which still remain undiscovered. Although labour force growth had a negative, significant impact on economic growth in the regression analysis, causality analysis revealed that growth in labour force Granger causes rural people’s access to improved sanitation facilities homogenously across countries. Hence, technological developments and other investments in human capital can help improve the productivity of labour and thereby facilitate its contribution to economic growth in South Asia.